Reducing carbon emissions in business through Responsible Management Education: Influence at the micro-, meso- and macro-levels. Issue 1 (March 2020) - Molthan-Hill, Petra; Robinson, Zoe P.; Hope, Alex; Dharmasasmita, Aldilla; McManus, Ella
Abstract: There has long been an understanding that to achieve meaningful progress against sustainability challenges, action is required at multiple levels. With regards to education initiatives, these levels range from macro-level international agreements and activities such as the United Nations Sustainable Development Goals (SDGs) and the United Nations Principles of Responsible Management Education, meso-level influences such as the role of national bodies supporting sustainability in higher education, and micro-level influences such as the commitment of individual universities or departments. However, decision makers are individuals and the development and delivery of such initiatives requires action at the level of the individual. This paper explores the impact of working within and across these different levels and how jointly they help to work towards addressing carbon reductions in a partnership setting between a business school and various organisations. In its centre is an educational initiative carried out in the United Kingdom in the core curriculum of Nottingham Business School where students conduct a carbon footprint of an organisation and recommend measures to reduce the company's greenhouse gas emissions. The total recommended greenhouse gas emissions savings from two years of the project were 507, 435 kg CO2 e, averaging over 10 tonnes per organisation and 2 tonnes per student. If this project was extended over 5 years and taken on by an additional educator, the potential reductions increase to 2, 562, 418 kg CO2 e. It demonstrates that action undertaken at the micro-level can result in significant impact at the macro-level when scaled up and provide significant benefits to actors across all levels from individuals though to all participating organisations. This initiative has proven very successful in delivering SDG 7, SDG 13 and SDG17; if taken up by more business schools the impacts on the targets of these SDGs and the climate change agreements could be significant. Highlights: Sustainability challenges require action across levels - individuals (micro), national (meso), to international (macro). Educational initiatives and business schools can drive significant carbon reductions in businesses through partnership. Greenhouse gas emission savings from student recommendations over two years of the project were 507, 435 kg CO2 e. If run over 5 years and replicated by one additional educator, the recommended reductions increase to 2, 562, 418 kg CO2 e. Action undertaken at the micro-level can have significant impact if scaling up is supported by higher level activity.